2011
DOI: 10.1016/j.jhevol.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of tool production, use, and hafting in Palaeolithic assemblages from Northeast Africa

Abstract: A detailed microwear study was performed on several assemblages from Northeast Africa to provide an anthropological scenario of late middle and upper Pleistocene populations in the Nile Valley and adjacent zones. Results are presented from the wear analysis of five sites, and an interpretation is provided of the keystones of MSA behaviour and its evolution throughout about 150,000 years. Locally available raw materials were predominantly used. Different tool uses were identified based on wear evidence, and it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(66 citation statements)
references
References 64 publications
1
62
0
3
Order By: Relevance
“…In Eurasia and Africa, complex technological processes were applied in order to haft MP points (Lombard et al 2005;Shea 1993;Wadley et al 2009). However, flakes and retouched items, not necessarily used in fauna-related activities, were hafted in similar manners (e.g., Boëda et al 2008;Friedman et al 1994-5;Rots 2013;Rots et al 2011). MP stone tools, armatures among them, likely had multiple uses (e.g., Holdaway 1989;Plisson and Beyries 1988;Shea 1988Shea , 1991; and see reviews in Dibble et al 2017;Nelson 1991).…”
Section: A Functional Impassementioning
confidence: 99%
“…In Eurasia and Africa, complex technological processes were applied in order to haft MP points (Lombard et al 2005;Shea 1993;Wadley et al 2009). However, flakes and retouched items, not necessarily used in fauna-related activities, were hafted in similar manners (e.g., Boëda et al 2008;Friedman et al 1994-5;Rots 2013;Rots et al 2011). MP stone tools, armatures among them, likely had multiple uses (e.g., Holdaway 1989;Plisson and Beyries 1988;Shea 1988Shea , 1991; and see reviews in Dibble et al 2017;Nelson 1991).…”
Section: A Functional Impassementioning
confidence: 99%
“…Lithic use-wear analysts create experimental collections of tools that consist of rawmaterials, hafting/prehension arrangements, and use-intensity that are deemed analogous to the time period and archaeological culture under investigation (Rots et al, 2011). Usewear analysts then use a combination of microscopic polishes, striations, "bright spots", and edge scarring/dulling to infer the life history of a tool by comparison with observations from the experimental collection.…”
Section: Inferring Tool Functionmentioning
confidence: 99%
“…Although this is roughly equivalent to a "random" distribution, the term "uniform" is used for these analyses to clarify that the comparison was not randomly sampled or resampled, but simply a uniform distribution of edge damage along the tool edge. Many experimental studies have demonstrated that damage from different activities creates different edge-wear distributions (Tringham et al, 1974;Keeley, 1980;Rots et al, 2011) and the KS statistic helps tease apart these processes based on the observed damage patterning.…”
Section: Cumulative Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). The extraction was made using hartebeest and gazelle horn picks, as well as bifacial lithic adzes of the "Nazlet Khater type," found within the prehistoric dump, which left utilization traces on the extraction walls (Vermeersch et al 2002;Rots et al 2011) (Fig. 3j).…”
Section: Nazlet Khatermentioning
confidence: 99%